2009
DOI: 10.1017/s095457940900025x
|View full text |Cite
|
Sign up to set email alerts
|

Relations of parenting style to Chinese children's effortful control, ego resilience, and maladjustment

Abstract: The purpose of the study was to examine the relations of authoritative parenting and corporal punishment to Chinese first and second graders' effortful control (EC), impulsivity, ego resilience, and maladjustment, as well as mediating relations. A parent and teacher reported on children's EC, impulsivity, and ego resilience; parents reported on children's internalizing symptoms and their own parenting, and teachers and peers reported on children's externalizing symptoms. Authoritative parenting and low corpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 127 publications
(230 reference statements)
9
82
1
7
Order By: Relevance
“…Similar result also found in a study done by Eisenberg, Chang, Ma & Huang [46]. Among Chinese participants, positive parenting style was associated with better effortful control while authoritarian parenting style associated negatively with effortful control.…”
Section: Acta Psychopathologica Issn 2469-6676supporting
confidence: 89%
“…Similar result also found in a study done by Eisenberg, Chang, Ma & Huang [46]. Among Chinese participants, positive parenting style was associated with better effortful control while authoritarian parenting style associated negatively with effortful control.…”
Section: Acta Psychopathologica Issn 2469-6676supporting
confidence: 89%
“…Prior studies of school-age children (e.g., Eisenberg et al 2009;Valiente et al 2006;Zhou et al 2004) have supported mediation models, wherein associations between parenting behavior and children's externalizing problems have been mediated by individual differences in child effortful control. However, consistent with findings from a large study of 3-year-old children (Olson et al 2005), in all three countries child inhibitory control and maternal harsh discipline made significant independent contributions to early externalizing problems, supporting an additive model of association.…”
Section: Discussionmentioning
confidence: 97%
“…For example, studies have shown that Chinese parents' power assertive discipline (e.g., frequent use of prohibitions, direct commands without explanations) with their toddler-age children predicted high levels of child aggression 2 years later, whereas inductive discipline was associated with low levels of aggression (Chen 2002 andWang et al 2006). Similarly, in Chinese families of school-age children, power assertive parenting has been linked with low levels of child inhibitory control, and with high levels of child anger/frustration ) and aggressive behavior (Eisenberg et al 2009;Nelson et al 2006). …”
Section: Early Socialization Experiencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Así, un estilo de crianza caracterizado por afecto y por apego seguro, propicia el desarrollo de habilidades sociales y con ello las relaciones positivas con los pares, y a su vez disminuye la probabilidad de que se presenten problemas conductuales (Eisenberg, 2009;Ensor & Hughes, 2008). Del mismo modo, la ausencia o excesiva supervisión y protección de los escolares por parte de sus padres y madres, ha sido vinculada a la irrupción de comportamientos inapropiados en distintas etapas del desarrollo (Foster, Garber, & Durlak, 2008).…”
Section: Introductionunclassified